STATIC ANALYSIS AND STRUCTUREOPTIMIZATION OF THE 18 m~3 CONCRETEMIXING TRUCKSUBFRAME - SHI WeiChao; WANG LiJie; DUAN XiaoFeng (Jixie qiangdu)
In view of the 18 m~3 concrete mixing truck subframe has failure problem,based on the feasibility ofestablishing the subframe mechanical model,using the finite element to analyze the subframe static. Established the subframe finite element model,determined the different conditions in the working process of the mixer truck,it obtained the distribution of stressstrainunder different working condition through analysis the subframe static characteristic,the result of analysis indicated that there was failure phenomenon in maximum stress area of subframe under three working condition. Aimed at reducing stress and weight,it designed topological Optimization algorithm for optimizing the subframe structure,analyzed the light weighting result and stress statics characteristic of optimized subframe,the result indicated that the stress and weight of the optimized subframe lower than before,the failure problem of maximum stress areahas been solved,the optimized subframe can satisfy the enterprise design requirements.